ANALISIS SEMIOTIKA ROLAND BARTHES - Sudariyah Sudariyah (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
Da'wah through film is considered effective because film has advantages that other media do not have. Film media has advantages as a propaganda medium. Da'i in conveying his da'wah message can be played by a player character in a film production, it doesn't have to be a lecture like taklim. Indirectly, the audience does not feel that they are being lectured on. Da'wah messages in films are easier to convey to the public. The research used is qualitative research. This study describes how Roland Barthes's Semiotics analysis is contained in the film "Laa Tahzan" by Danial Rifki. Analysis of the film Laa Tahzan is presented in the form of image fragments using Roland Barthes' semiotic analysis. As a Muslim, you can determine a firm stance on invitations to follow the procedures for worship of other religions in a good way. That an Indonesian Muslim can survive in a foreign country (Japan) to be able to defend his faith and the level of trials in life remains the same and will apply as long as we live. It is certain that interfaith marriages will not be possible to realize the Sakinah family as the main purpose of carrying out marriages. In Islam, there are clear laws regarding marriage. Advise everyone who will marry should pay attention to the prospective bride.